Effects of silver nanoparticles on bacterioplankton in a boreal lake. (29th June 2016) - Blakelock, Graham C.; Xenopoulos, Marguerite A.; Norman, Beth C.; Vincent, Jennifer L.; Frost, Paul C.
Summary: Silver nanoparticles (AgNPs) are widely used antimicrobial agents and a growing body of evidence suggests that their release into aquatic environments threatens natural bacterial communities and whole ecosystems. However, a knowledge gap exists between the toxic effects of AgNPs found in laboratory studies and their potential impacts in natural environments. In an enclosure experiment conducted in a boreal lake, we exposed natural bacterial communities to AgNPs with two common types of coatings (polyvinylpyrrolidone (PVP) and citrate) under two different exposure regimes, a one‐time (pulse) and a continuous (chronic) addition. AgNP additions increased Ag concentrations to nearly 50 μg L −1 in the highest treatments. We examined bacterial responses (abundance, biomass, production, chlorophyll‐ a content and nutrient stoichiometry) over the course of 6 weeks in the summer of 2012. Bacterioplankton exposed to AgNPs initially accumulated Ag over the experimental period regardless of AgNP concentration or coating. After the initial period of increase, Ag in the bacterial size fraction changed largely in concert with bacterial biomass. We found no toxic effects of AgNPs on bacterioplankton abundance, biomass, production or chlorophyll‐ a content throughout the experiment. Bacterial production was greater after the pulse addition of PVP‐coated AgNPs and in the chronic addition of PVP‐coated AgNPs at the highest concentrations. Furthermore, AgNPs produced no significant changes in nutrient stoichiometry of the bacterioplankton size fraction. This lack of effects of AgNPs on lake bacterioplankton observed under the natural conditions studied here differs from results of short‐term and laboratory studies of single‐species bacterial cultures. Our results thus indicate AgNP effects in lakes may be less than expected based on standard laboratory experiments, and that additional studies are needed to understand AgNP toxicity under realistic natural conditions in lakes and other ecosystems.